2007
DOI: 10.1002/adfm.200600866
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Modified Macroporous Membrane Prepared by using Pulsed Laser Deposition

Abstract: Pulsed laser deposition (PLD) is used to deposit pure metals (Pt and Au) and a mixture of metals (Pt–Ru) at the surface of a porous aluminum anodic oxide (AAO) substrate. In the case of Pt, thick films (> 300 nm) with pore diameters larger than 150 nm (macroporous), replicating the pore structure of the underlying AAO substrate, are obtained when PLD is performed at high (> 50 eV at–1) kinetic energy (Ek) conditions. At lower Ek conditions, the characteristic structure of the AAO membrane is not discerna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…As the pressure in the deposition chamber is increased, the likelihood for the plasma species to lose part of their kinetic energy through a contact (collision) with the gas molecules will be also increased, thus lowering the kinetic energy of the plasma species. This variation of the kinetic energy of the plasma species induces a modification of the surface mobility of the deposited species [11]. It has been demonstrated elsewhere that the growth of Pt nanoparticles is governed by surface diffusion mechanism when PLD is performed in presence of an He background gas at pressure below 0.5 Torr [12].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As the pressure in the deposition chamber is increased, the likelihood for the plasma species to lose part of their kinetic energy through a contact (collision) with the gas molecules will be also increased, thus lowering the kinetic energy of the plasma species. This variation of the kinetic energy of the plasma species induces a modification of the surface mobility of the deposited species [11]. It has been demonstrated elsewhere that the growth of Pt nanoparticles is governed by surface diffusion mechanism when PLD is performed in presence of an He background gas at pressure below 0.5 Torr [12].…”
Section: Resultsmentioning
confidence: 97%
“…Higher surface mobility of the deposited species translates into denser films and surface rearrangement that yield to minimization of the energy. This effect has been revealed to activate during the deposition of Pt, Au, and Pt-Ru films [11].…”
Section: Resultsmentioning
confidence: 98%
“…The effect of the background pressure on the morphology of deposits is reported in the work of Pereira et al 18 The Pt loadings as estimated by thermogravimetric analysis (TGA) were about 0.18, Prior to the electrochemical measurements in methanol, the surface of the working electrode was cleaned electrochemically by potential cycling in 0.5 M H 2 SO 4 . Before each test, dissolved oxygen was removed from the solution by bubbling argon through the solution for 20 to 30 min.…”
Section: Methodsmentioning
confidence: 95%
“…Meanwhile, rotation of the membrane during evaporation ensured the uniformity of the resultant materials. In another approach, Pereira et al [117] reported on a simple process for the formation of a functionally modified AAO channel by using pulsed laser deposition (PLD) method to deposit a metal (i.e. Au, Pt) or a mixture of metal (i.e.…”
Section: Thermal Vapour Depositionmentioning
confidence: 99%